The Fiscal Dimensions of Adjustment in Low-Income Countries - Gupta, Sanjeev (Occasional Papers; Occasional Paper ;, 1992)
A strengthened fiscal position is at the core of most economic adjustment programs supported by IMF lending, especially for the poorer countries that draw on the IMF's structural adjustment facilities. This paper reviews developments in 23 countries and evaluates their experience with fiscal and structural adjustment, including their efforts to design social safety nets to cushion the effects of adjustment.